New Marketing Strategy For Tatuis Mukena Fashion - Putri, Dwidania Sabarina; Paramarta, Riawan B (The Indonesian Journal of Business Administration, 2014)
Abstract - Tatuis is a company pioneered the mukena fashion industry in Indonesia. Mukena and sajadah fashion first launched by Tatuis on 2010 brought changes in the national mukena industry. At that time, the mukena on the market generally in plain white color. Variance of mukena design is evolving due to moslem womanâ€™s taste which more fashion sensitive. How is the marketing strategy of Tatuis in maintaining its position as the mukena fashion pioneer in Indonesia? How Tatuis increase their brand awareness in the market? How Tatuis increase their sales number? How Tatuis face the competitor in the future? Research started with the analysis of the current business situation. The research then combine with the relevant theories and completed with market research of mukena customer in Jakarta. Based on the research analysis using relevant theories and market research analysis, the author proposed to do the market penetration strategy. The result of the analysis found that market penetration strategy is the most suitable marketing strategy for Tatuis mukena fashion. The reasons for selecting market penetration strategy is because the business still on growth stage, the market share is great but still can be improved in order to obtain new customer from the existing segment. Author found that the best business strategy for Tatuis is differentiation strategy. The reason for selecting the differentiation strategy based on the character of the industry, where the product is the main factor that will attract the customer to buy their products and the tough competition among the players. The differentiation strategy will focus on the value received by the customer through their elaboration of product features. This strategy will take Tatuis to a position where competitor will not easily match. The condition will make Tatuis position as the leader in mukena fashion industry hardly rivaled by the competitor.Â Keyword : fashion, mukena, moslem, marketing strategy, business strategy, Marketing Mix, market penetration strategy, differentiation